THE INFLUENCE OF THE ROLE OF SAVINGS AND LOAN COOPERATIVES ON THE DEVELOPMENT OF UMKM - Hidayatullah, M. Alief (IJMA (Indonesian Journal of Management and Accounting), 2024)
This research aims to determine the role of the Minhajus Sa Adah Hakiki Sharia Cooperative in the development of cooperative members' micro, small and medium enterprises, looking at the aspect of business income before and after obtaining credit from the Minhajus Sa Adah Hakiki Sharia Cooperative and the work productivity of cooperative members. This research was analyzed using quantitative analysis methods using the t-test and the Mann-Whitney difference test. Based on the calculation results of the data analysis method with the decision rule if: Thit > Ttab at α = 0.05. So Ho is accepted and if Thit < Ttab at α = 0.05. So Ho was rejected. With the calculation results above, Thit is obtained at 4.138 > Ttab 2.018, so from this result Ho is accepted. By accepting Ho, the research results show that the work productivity of cooperative members has a role in increasing the business development of UMKM players. The significance value of member Micro, Small and Medium Enterprises turnover before and after using the credit role of the Minhajus Sa Adah Hakiki Sharia Cooperative is 0.156. With these results, it can be said that the Minhajus Sa Adah Hakiki Sharia Cooperative has an important role in increasing the turnover of UMKM